Pengelolaan Sampah Di Pasar Tradisional Terong Kota Makassar - S, Rostina; Rasman, Rasman; Everlita, Lulu (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Waste is a by-product of human activity that has the potential to pollute the environment. Waste is a common problem in almost all conventional markets in Indonesia. If waste is not disposed of properly and accumulates in one location, it can cause air pollution, aesthetic problems and health risks. Organic waste, in particular, can cause the rapid spread of germs and disease vectors due to its potential for contamination. The aim of this research is to assess waste management practices at the Terong Traditional Market located in Makassar City. The type of research used is a cross-sectional study with a descriptive analytical observational approach to evaluate the condition of waste management at the Terong Traditional Market at a certain time. The sampling technique for this research is Simple Random Sampling with a sample size of 200 respondents.  The data analysis technique was carried out using statistical tests, namely, Chi Square. The results of the research show that the Chi Square Test value obtained was ρ = 0.001 < 0.05 for the waste storage, collection and transportation variables so it can be concluded that there is a relationship between waste storage, waste collection, waste transportation and waste management at the Terong Traditional Market in Makassar City.  Waste management at the Terong Traditional Market in Makassar City is considered inadequate according to Minister of Health Regulation No. 17 of 2020. It is recommended that traders and market managers be actively involved in sorting organic and inorganic waste to make the waste processing process at the landfill more effective. Keywords: Waste management, traditional markets